Digital Transformation and the Future of Islamic Educational Management for Sustainable Development in Pakistan - Zohaib Hassan Sain; Aydin Anar Babayev; Duli Pllana; Alma Vorfi Lama (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
ENGLISH: Digital Transformation and the Future of Islamic Educational Management for Sustainable Development in PakistanObjective: This study examines the impact of digital transformation on Pakistani Islamic educational institutions and proposes a sustainable governance model aligning technological innovation with Islamic values. Method: Utilizing a qualitative document-based institutional case study analyzed through Critical Policy Analysis and Socio-Technical Systems theory, national policies and institutional records were evaluated. Results: Findings reveal a major disconnect between centralized digitalization mandates and local madrasa infrastructural capacities, where fragmented governance, heavy administrative loads, educator technostress, and privacy issues severely impede implementation. Conclusion: Sustainable digital transformation demands an adaptive governance framework integrating core values such as Amanah, Shura, and 'Adl with context-sensitive technology and secure offline-first systems. Contribution: This study contributes an Adaptive Sustainable Governance Model to advance Islamic educational management and support inclusive digital progress toward Sustainable Development Goal 4.INDONESIA: Transformasi Digital dan Masa Depan Manajemen Pendidikan Islam untuk Pembangunan Berkelanjutan di PakistanTujuan: Penelitian ini menganalisis dampak transformasi digital terhadap lembaga pendidikan Islam di Pakistan serta merumuskan model tata kelola berkelanjutan yang menyelaraskan inovasi teknologi dengan nilai nilai Islam. Metode: Menggunakan studi kasus institusional berbasis dokumen kualitatif yang dianalisis melalui pendekatan Critical Policy Analysis dan teori Socio Technical Systems, kebijakan nasional dan arsip institusi dievaluasi secara sistematis. Hasil: Temuan menunjukkan ketidaksesuaian mendasar antara mandat digitalisasi pemerintah pusat dan kapasitas infrastruktur madrasah lokal, di mana tata kelola yang terfragmentasi, beban administratif yang berat, technostress pendidik, serta masalah privasi menghambat implementasi secara signifikan. Kesimpulan: Transformasi digital yang berkelanjutan memerlukan kerangka kerja tata kelola adaptif yang mengintegrasikan nilai nilai inti seperti Amanah, Syura, dan Adl dengan teknologi peka konteks serta sistem offline first yang aman. Kontribusi: Penelitian ini menyumbangkan Adaptive Sustainable Governance Model untuk memajukan manajemen pendidikan Islam dan mendukung kemajuan digital yang inklusif menuju Sustainable Development Goal 4.